2017
DOI: 10.1080/03014460.2017.1371222
|View full text |Cite
|
Sign up to set email alerts
|

Mutation rates for 20 STR loci in a population from São Paulo state, Southeast, Brazil

Abstract: Short tandem repeats (STRs) are genetic markers largely employed in forensic analysis and paternity investigation cases. When an inconsistency between the parent and child is considered as a possible mutation, the mutation rate should be incorporated into paternity index calculations to give a robust result and to reduce the chance of misinterpretation. The aim of this study was to estimate the mutation rates of 20 autosomal STRs loci used for paternity tests. In these loci we analysed 29,831 parent-child alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
3
6
1
2
Order By: Relevance
“…Results obtained in the present study are similar to those reported in two other studies performed in Brazilian populations , regarding the paternal::maternal proportion of mutation origin. Our findings presented the mutation rate generated by paternal meiosis (1.8 × 10 −3 ) was six times higher than the maternal one (0.3 × 10 −3 ), even though we have detected 29 discrepant alleles with ambiguous origin (Table ).…”
Section: Slippage Mutations Observed In 5171 Paternity Cases From Indsupporting
confidence: 92%
See 4 more Smart Citations
“…Results obtained in the present study are similar to those reported in two other studies performed in Brazilian populations , regarding the paternal::maternal proportion of mutation origin. Our findings presented the mutation rate generated by paternal meiosis (1.8 × 10 −3 ) was six times higher than the maternal one (0.3 × 10 −3 ), even though we have detected 29 discrepant alleles with ambiguous origin (Table ).…”
Section: Slippage Mutations Observed In 5171 Paternity Cases From Indsupporting
confidence: 92%
“…Based on the number of meiosis per locus, the overall mutation rate determined in this study for the 15 forensic STR loci was 1.3 × 10 −3 (95% CI: 1.1–1.5 × 10 −3 ), which is a similar value to the findings of previous studies with Brazilian populations of the Southern and Southeastern regions , and with Polish and Southern Chinese Han populations, which ranged from 1,18 × 10 −3 to 1,39 × 10 −3 . The mutation rate calculated in this study is, however, slightly different from an earlier study including Southern, Southeastern and Central Brazilian populations (0.94 × 10 −3 ) and data published for the Northeastern region of the country (0.75 × 10 −3 ) , and much higher than the rate reported in a recent study analyzing a population from Central Brazil (0.21 × 10 −3 ) .…”
Section: Slippage Mutations Observed In 5171 Paternity Cases From Indsupporting
confidence: 87%
See 3 more Smart Citations